2016
DOI: 10.1002/prp2.223
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical animal anxiety research – flaws and prejudices

Abstract: The current tests of anxiety in mice and rats used in preclinical research include the elevated plus‐maze (EPM) or zero‐maze (EZM), the light/dark box (LDB), and the open‐field (OF). They are currently very popular, and despite their poor achievements, they continue to exert considerable constraints on the development of novel approaches. Hence, a novel anxiety test needs to be compared with these traditional tests, and assessed against various factors that were identified as a source of their inconsistent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 260 publications
(356 reference statements)
3
81
1
1
Order By: Relevance
“…At the end of the infusion period, all animals, independent of treatment, showed a reduction in rearing, but not in the locomotor activity, which is attributable to the animal’s habituation to the equipment as can be observed for some behavioral equipments [26]. …”
Section: Resultsmentioning
confidence: 99%
“…At the end of the infusion period, all animals, independent of treatment, showed a reduction in rearing, but not in the locomotor activity, which is attributable to the animal’s habituation to the equipment as can be observed for some behavioral equipments [26]. …”
Section: Resultsmentioning
confidence: 99%
“…It can be argued that the ability to demonstrate anxiety‐like behavior in the EPM was limited due to the low values in the control rats. Several factors may influence the behavior of rats on the EPM including but not limited to lighting, animal handling, time of the test, the number of trials, and strain (Carobrez and Bertoglio, 2005; Ennaceur and Chazot, 2016). However, the values that we have obtained in the present study are consistent with previous studies utilizing similar subjects (SD rats) and EPM protocol (Elliott et al, 2004; Inostroza et al, 2011; Schmitt and Hiemke, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Affective withdrawal symptoms were assessed through the elevated plus-maze (EPM) test, open-field test (OFT), and the passive-avoidance task. The EPM is a widely used and accepted method to assess anxiety-like behavior in rodents (Carobrez and Bertoglio, 2005;Ennaceur and Chazot, 2016). Previous studies have shown that rats undergoing nicotine withdrawal demonstrate anxiety-like behavior in this test (Irvine et al, 2001;Manhaes et al, 2008;Wilmouth and Spear, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated platform with downward slopes, unlike the plus-maze, light/dark box, and the open-field, does not provide a refuge or a shelter, which promote safety and security over risk taking [24,21]. The presence of protected/unlit spaces may reduce fear and anxiety [50]; the decision-making is simplified by the availability of the choice between an apparent safe place and an apparent aversive place.…”
Section: D 21mentioning
confidence: 99%